Going, going, gone: Landscape drying reduces wetland function across the American West - J. Patrick Donnelly; Johnnie N. Moore; John S. Kimball; Kelsey Jencso; Mark Petrie; David E. Naugle (Ecological Indicators)
Ecosystems are rapidly transforming into non-historical configurations as a nearly inevitable consequence of climate and land use change. Water scarcity, in particular, is emerging as a new and powerful threat, forcing wetland ecosystems into altered functional states as the frequency and duration of their inundation diminish. Potential for large-scale functional loss raises concerns over environmental sustainability, as wetlands are key determinants of biodiversity in water-limited landscapes. To improve our understanding of rapid ecosystem change, we reconstructed monthly wetland surface water hydrology in the western U.S. from 1984 to 2023 using cloud computing and ∼ 150,000 satellite images to measure shifts in the timing and duration of inundations. Monitoring encompassed all freshwater palustrine and littoral systems, including anthropogenic wetlands sustained through human water use (e.g., irrigated agriculture and earthen livestock ponds). Wetland surface water was classified annually by hydroperiod (semi-permanent, seasonal, and temporary) based on monthly inundation rates and binned into functional groups based on ecological and anthropogenic associations to track patterns of change. Results were summarized at an ecoregional level to normalize heterogeneity in landscape drivers structuring trends. Findings showed that overall wetland abundance (i.e., inundated area) changed by only 0.2 % during the forty-year study period; however, shortened inundation periods reduced semi-permanent wetlands by 24 % and increased the combined abundance of seasonal and temporary wetlands by a nearly equal amount (23 %). Trends suggest that semi-permanent loss acts as an early indicator of large-scale functional decline, signaling wetland ecosystems’ transition along a continuum of persistent to more ephemeral states. Functional declines were heterogeneous, with losses and gains focused in a limited number of ecoregions. High rates of semi-permanent loss were associated with overall declines in wetland abundance at the ecoregional level that exceeded 20 % in some cases. Anthropogenic water use supported half the wetland resources measured. Proliferating agricultural-wetlands and earthen livestock ponds were drivers of wetland expansion and indicators of human adaptation to water scarcity that offset natural-wetlands losses in some ecoregions. Our analysis identifies a shortfall in large-scale governmental monitoring programs that remain focused on historical wetland threats associated with agricultural drainage and urban expansion. Outcomes from this work improve our understanding of environmental change, elevating the urgency of developing adaptive conservation strategies in light of the rapidly evolving trajectory of wetland ecosystems in the western U.S.